1998
DOI: 10.1016/s0969-2126(98)00136-1
|View full text |Cite
|
Sign up to set email alerts
|

The structure of an insect parvovirus (Galleria mellonella densovirus) at 3.7 å resolution

Abstract: The sequence of the glycine-rich motif, which occupies each of the channels along the fivefold axes in vertebrate viruses, is conserved between mammalian and insect parvoviruses. This motif may serve to externalize the N-terminal region of the single VP1 subunit per particle. The domain swapping of the N termini between insect and vertebrate parvoviruses may have the effect of increasing capsid stability in GmDNV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 40 publications
3
118
0
Order By: Relevance
“…The first few parvovirus capsid structures to be solved were the canine parvovirus [Tsao, J et al, 1991], followed by feline panleukopenia virus [Agbandje, M et al, 1993], B19 [Chipman, PR et al, 1996;Kaufmann, B et al, 2004], the minute virus of mice (MVM) [Llamas-Saiz, AL, 1997] and Galleria mellonella densovirus [Simpson, AA et al, 1998]. The structural details from these parvovirus capsids have been used as a foundation for many AAV studies because of their structural similarity in several domains.…”
Section: Capsid Crystal Structure: So Much To Learnmentioning
confidence: 99%
“…The first few parvovirus capsid structures to be solved were the canine parvovirus [Tsao, J et al, 1991], followed by feline panleukopenia virus [Agbandje, M et al, 1993], B19 [Chipman, PR et al, 1996;Kaufmann, B et al, 2004], the minute virus of mice (MVM) [Llamas-Saiz, AL, 1997] and Galleria mellonella densovirus [Simpson, AA et al, 1998]. The structural details from these parvovirus capsids have been used as a foundation for many AAV studies because of their structural similarity in several domains.…”
Section: Capsid Crystal Structure: So Much To Learnmentioning
confidence: 99%
“…Capsid structures of various parvoviruses have been resolved by X-ray crystallography or electron cryomicroscopy (1,2,3,37,40,42,59,66,71,79,83,84). All of these particles show similar structural arrangements at the inner surface.…”
mentioning
confidence: 99%
“…The observations that parvoviruses replicate in the nucleus, closely in tune with the physiology of the host cell, and are able to do so with both vertebrate and invertebrate cells, suggest that vertebrate and invertebrate parvoviruses may be more different than usually accepted. Indeed, when recently the first 3D structure of an invertebrate parvovirus was solved by X-ray crystallography (Simpson et al, 1998), major differences were observed between the two virus groups. Despite many differences in the molecular biology of these virus groups, it is surprising how many aspects of their genome organization and molecular biology are shared, justifying their classification as one family.…”
Section: Tijssenmentioning
confidence: 99%
“…The 3D structures of several vertebrate parvoviruses (CPV, FPV, MVM) and, recently, of an invertebrate parvovirus (GmDNV) have been solved to nearatomic resolution using X-ray crystallography (Simpson et al, 1998). All have a common structure arranged with T = 1 icosahedral symmetry with each subunit having the same eight-stranded anti-parallel >-barrel motif (Fig.…”
Section: Three-dimensional Structure Of Parvovirusesmentioning
confidence: 99%